Emergency contraceptive use of Metronidazole among University female students in Dodoma region of Tanzania: a descriptive cross-sectional study - Nipael M. Samson; Emmanuel Izack Sumari; Valence Ndesendo; Romuald Mbwasi (BMC, 2023)
Abstract Background Metronidazole is known for its therapeutic effect as antibacterial and anti-parasitic. However, its toxicity on the reproductive system remains unclear. Metronidazole use in rodents is associates with toxic effects on the reproductive system, including hormonal alterations, reduced number of fertile cells and reduced sites for implantation, size of the placental disc area, constituent elements of the labyrinth, and spongiotrophoblast layers. Its use at a therapeutic dose among humans has been associated with an increased risk of spontaneous abortion. The effects on the reproductive system in humans may result in misconceptions about contraceptive effects hence sexually active individuals like students who, for any reason, fail to access safe contraceptive services use any possible methods to protect them from conception. This study aims to investigate the unofficial (un-prescribed) use of Metronidazole as an emergency contraceptive and some of its associated factors. Methods This quantitative cross-sectional study involved 470 participants where stratified random sampling technique was used to obtain the sample from three educational institutions in the Dodoma Municipal, Dodoma region. Collected data were analyzed using SPSS version 25, descriptive statistical analysis was done to determine frequencies, percentages, and association, p < 0.05 was used to determine statistical significance. Further analysis using Multivariate binary logistic regression was done to determine the nature of the association between the study variables. Results The finding shows that 169(62.4%) use Metronidazole as an emergency contraceptive. Notably, 345(73.4%) stated that they had ever heard someone use Metronidazole for contraception, especially their peers. Furthermore, an increase in the year of study was significantly associated with reduced use of Metronidazole as an emergency contraceptive (B = [-0.45], p = [0.02]). Furthermore, an increase in age, studying in non-medical college/university, the experience of using contraceptive methods, and hearing someone ever used Metronidazole was found to be positively associated with its use as an emergency contraceptive, although not statistically significant. Conclusion Metronidazole was found to be used as an emergency contraceptive in high doses, different factors associated with its use, and reasons influencing its use. Further research may be done to explore the toxicological effect of high doses of Metronidazole as a contraception and compare the efficiency of Metronidazole over other emergency contraceptives.